The Role of Triglycerides in Atherosclerosis: Recent Pathophysiologic Insights and Therapeutic Implications - Akivis, Yonatan; Alkaissi, Hussam; McFarlane, Samy I.; Bukharovich, Inna (Current Cardiology Reviews, 2024)
Triglycerides have long been recognized as a cardiovascular disease risk factor. However, their precise role in atherosclerosis and potential utility as a therapeutic target remains debated topics. This review aims to shed light on these aspects by exploring the complex relationship between triglycerides and atherosclerosis from pathophysiological and pharmacological perspectives. Triglycerides, primarily carried by chylomicrons and very low-density lipoproteins, play an essential role in energy storage and utilization. Dysregulation of triglyceride homeostasis and triglyceride- rich lipoproteins metabolism often leads to hypertriglyceridemia and subsequently increases atherosclerosis risk. Triglyceride-rich lipoproteins remnants interact with arterial wall endothelial cells, get retained in the subendothelial space, and elicit inflammatory responses, thereby accelerating atherogenesis. Despite the clear association between high triglyceride levels and increased cardiovascular disease risk, intervention trials targeting triglyceride reduction have produced mixed results. We discuss a range of triglyceride-lowering agents, from fibrates to omega-3 fatty acids, with a focus on their mechanism of action, efficacy, and major clinical trial outcomes. Notably, the role of newer agents, such as angiopoietin-like protein 3 and apolipoprotein C3 inhibitors, is also explored. We highlight the challenges and controversies, including the ongoing debate on the causal role of triglyceride in atherosclerosis and the discordant outcomes of recent clinical trials. The potential confounding effects of associated risk factors, such as elevated apolipoprotein B, insulin resistance, and metabolic syndrome, are considered. In conclusion, this review underscores the importance of a nuanced approach to understanding the role of triglycerides in atherosclerosis and their potential as a therapeutic target. Further research is needed to unravel the complex interplay between triglycerides, triglyceride-rich lipoproteins, and associated factors in atherosclerosis pathogenesis and refine triglyceride-targeted therapeutic strategies.
Keywords: cardiovascular disease